2008
DOI: 10.1021/la800479k
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle X-ray Scattering and Rheological Characterization of Aqueous Lignosulfonate Solutions

Abstract: Lignosulfonate is a colloidal polyelectrolyte widely used as a dispersant in various industrial applications and produced during chemical pulping of wood chips. Here we present a systematic small-angle X-ray scattering (SAXS) and rheological study of fractionated lignosulfonate (mass weighted molar mass M w 18 000 g/mol) dissolved in water and 0.2 M NaCl. The concentration range varied from semidilute to concentrated regime. SAXS intensity of all solutions followed the Porod law at all concentrations, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 63 publications
2
78
0
Order By: Relevance
“…It is an abundant renewable resource and a waste byproduct from the paper industry ( Figure 1). [12] The development of high-value applications of LS or lignin is one of the most important directions of modern biorefinery. [13] Recent research demonstrated that they can be used as proton-transfer materials for fuel cells [14] or electrochemistry materials due to their sulfonic acid functionality.…”
Section: Introductionmentioning
confidence: 99%
“…It is an abundant renewable resource and a waste byproduct from the paper industry ( Figure 1). [12] The development of high-value applications of LS or lignin is one of the most important directions of modern biorefinery. [13] Recent research demonstrated that they can be used as proton-transfer materials for fuel cells [14] or electrochemistry materials due to their sulfonic acid functionality.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity curves were measured with a HI-STAR area detector at a sample-to-detector distance of 50 cm. The magnitudes of the scattering vector k [k ϭ (4 sin)/, where 2 is the scattering angle and is the incident wavelength] were 0.02 to 0.42 Å Ϫ1 (34). The samples were centrifuged into pellets.…”
Section: Bacterialmentioning
confidence: 99%
“…Due to its heterogeneous nature, there is no well-defined critical micelle concentration. The viscosity of dense lignosulfonate solutions is high [5] and an interfacial lignosulfonate film is rigid and provides good film stability in emulsified systems, even in highly concentrated emulsions and in foams. One way to demonstrate this is to look at the compressibility of lignosulfonate films (Figure 14.3).…”
Section: Lignosulfonates As Stabilizers For Emulsions and Suspoemulsionsmentioning
confidence: 99%
“…A schematic drawing of the suggested branched structure is given in Figure 14.1. That lignosulfonates indeed are compact and rigid molecules was further elaborated by Vainio et al [5], who suggested that lignosulfonates are reminiscent of hyperbranched polymers that behave in a similar way to particles in solution. Similar conjectures have been published earlier [6,7].…”
Section: Introductionmentioning
confidence: 98%